Pedagogical evaluation in the area of physical education: a paradigm shift for today's Chile. (Revista horizonte, 2013)
This essay proposes a discussion on the basic aspects of evaluation in the area of education, focusing on the area of Chilean physical education. Visualizing in the analysis of the own pedagogical practices of the area, the incompatibility during the process of formation of a student and the evaluations as a preponderant function in the process of teaching and learning. Therefore, relevance is given to the identification of criteria that determine what will be observed within a pedagogical process, focused on the evaluative processes as obtaining valuable information to make decisions that help to improve either the teaching or the learning of students. This paper also aims to open a discussion about the evaluation traditionally developed and how it is inconsistent with current pedagogical principles.